The course of psychiatric co‐morbidity in patients with breast cancer – results from the prospective multi‐centre BRENDA II study. Issue 5 (11th September 2015) - Singer, Susanne; Schwentner, Lukas; van Ewijk, Reyn; Blettner, Maria; Wöckel, Achim; Kühn, Thorsten; Felberbaum, Ricardo; Flock, Felix; Janni, Wolfgang; Kreienberg, Rolf; ,
Abstract: Purpose: This study examined the frequency of psychiatric co‐morbidity in patients with breast cancer, its changes over time and predictors for these changes. Methods: In a prospective study with measurements before surgery (t1, baseline), 1 month (t2) and 8 months thereafter (t3) using the Patient Health Questionnaire, we examined the course of psychiatric co‐morbidity in breast cancer patients. The co‐morbidity courses were grouped into healthy (no co‐morbidity during the study), acute (co‐morbidity at t1 and/or t2, but not at t3), emerging (no co‐morbidity at t1, but at t3) and chronic (co‐morbidity at t1 and t3). Results: Of the 598 participants, 19% had acute, 10% emerging and 9% chronic psychiatric co‐morbidity. Acute co‐morbidity was more common in patients with poor quality of life (odds ratio (OR) 9.6, 95% confidence interval (CI) 4.4–20.8) and somatic co‐morbidity (OR 3.8, CI 1.1–12.4). Patients who perceived support from their doctors had acute co‐morbidity less frequently (OR 0.7, CI 0.5–1.0). Emerging co‐morbidity occurred more often in younger patients (OR 2.4, CI 1.2–4.7) and in patients with another cancer in their own (OR 2.0, CI 1.1–3.9) or family (OR 2.1, CI 1.1–4.3) histories, less often in patients with support from doctors (OR 0.6, CI 0.4–1.0). Chronic co‐morbidity was related to poor quality of life (OR 12.1, CI 3.6–39.9). Conclusion: We found acute and emerging psychiatric co‐morbidities less often in patients who reported having a supportive doctor–patient relationship. Patients that require psycho‐oncological support often have poor quality of life and have experienced cancer before. Copyright © 2015 John Wiley & Sons, Ltd.